2006
DOI: 10.1128/ec.5.4.712-722.2006
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum-Associated Degradation Is Required for Cold Adaptation and Regulation of Sterol Biosynthesis in the Yeast Saccharomyces cerevisiae

Abstract: Endoplasmic reticulum-associated degradation (ERAD) mediates the turnover of short-lived and misfolded proteins in the ER membrane or lumen. In spite of its important role, only subtle growth phenotypes have been associated with defects in ERAD. We have discovered that the ERAD proteins Ubc7 (Qri8), Cue1, and Doa10 (Ssm4) are required for growth of yeast that express high levels of the sterol biosynthetic enzyme, 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR). Interestingly, the observed growth defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 53 publications
2
16
0
1
Order By: Relevance
“…It has been shown to be involved in a number of human diseases [10][11][12] and in yeast, ERAD has been shown to be related with various stresses. The defect of UBC7 and UBC1 or the high expression of HRD1 affects yeast responses to Cd 2+ , a toxic ion to organisms [13]; doa10 and ubc7 mutants are more sensitive to cold than wild type (WT), perhaps through effects on sterol biosynthesis [9]; and overexpression of UBC1, UBC6, and UBC7 increases yeast tolerance to several stresses, including heat, H 2 O 2 , and canavanine [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to be involved in a number of human diseases [10][11][12] and in yeast, ERAD has been shown to be related with various stresses. The defect of UBC7 and UBC1 or the high expression of HRD1 affects yeast responses to Cd 2+ , a toxic ion to organisms [13]; doa10 and ubc7 mutants are more sensitive to cold than wild type (WT), perhaps through effects on sterol biosynthesis [9]; and overexpression of UBC1, UBC6, and UBC7 increases yeast tolerance to several stresses, including heat, H 2 O 2 , and canavanine [14].…”
Section: Introductionmentioning
confidence: 99%
“…The key components of the DOA10 complex are E2s, includ-ing UBC6 and UBC7, and RING finger type E3 ligase DOA10 [7]. Deletion of these genes would affect the ability of the organism to scavenge unfolded proteins [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…the yellow color in the corresponding merged images indicates co-localization of the co-expressed proteins at the er. Also shown (bottom row at the right) are representative images of a GFP-cb5 and rFP-er co-transformed cell, wherein overexpression (~20 h postbombardment) of GFP-cb5 has led to the formation of large, globular fluorescent er structures (indicated with arrowheads), which, based on the appearance of similar cb5-induced er structures in other published studies, 7,12,13 were presumed to be karmellae. (c) topology mapping of the GFP-cb5 reporter protein in er membranes.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…These globular structures were presumed to be karmalle, which are stacks of ER cisternae and are often induced by Cb 5 when overexpressed in eukaryotic cells. 7,12,13 While karmalle do not induce the unfolded protein response, 13 any BY-2 cells exhibiting these types of structures were discarded from our analysis of Fad3-GFP-Cb5 protein half-life. Investigation of protein degradation rates for the various fusion constructs revealed that GFP-Cb5 was moderately stable in plant cells, and notably, the degradation rate was not appreciably affected by inclusion of the proteasomal inhibitor MG132 (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Recientes estudios (Loertscher et al, 2006) han puesto de manifiesto la importancia en la respuesta al frío de una correcta regulación de la biosíntesis de ergosterol, puesto que es una adaptación fisiológica esencial que permite a la célula sobrevivir a bajas temperaturas. En dicho estudio se demuestra que la mutación en cualquiera de estas tres enzimas: Ubc7p, Cue1p y Doa10p, pertenecientes al sistema de degradación asociado al retículo endoplasmático (ERAD, por sus siglas en inglés: Endoplasmic Reticulum-alteración en el estado fisiológico de la célula causada por la disminución en el transporte a través de la membrana, la reducida actividad enzimática y la acumulación de proteínas con conformaciones anómalas.…”
Section: Respuesta Tempranaunclassified